Sementasi Pasar Produk Kosmetika untuk Kulit Wajah di Surabaya - Triwijayati, Anna (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2006)
Segmenting in marketplace is important to clasify consumer. Consumer's profile will lead firm to understand the target market. The aim of this study is segmenting customers cosmetic based on consumer perception. This research use descriptive research design without hypothesis. Data is collected by survey with questionaire, Samples are women who live in Surabaya. Data are analyzed by cluster analyze in order to get market segmentation variable. Results of this study are : l) Segment Profile L' steady consumer with deep knowledge of cosmetic, innovative, up to date and.foreign made orientation, other directed, enthusiast , inertia and soft core loyal, valuable, tend to have high dependently to face cosmetic, daily routine and high intens to use it. 2) Segment profile 2: Early and late majority and not up to date, less innovative and not familiar with cosmetic trend, realistic and moderate userale, etnocentris and inner directed, moderate knowledge of cosmetic and hard core loyal.3) Segment Profile 3: Late majority, less enthusiast, and laggard, inner directed, low knowledge of cosmetic, moderate awareness and moderate attitude, lower use rate and situational, soft core loyal.